Design and development of 123kV 13L Cross-arm with bracing structures for application in transmission towers - Sharaf, Sharaf Hussein Kadhim (2021)
In this study, experimental and numerical investigations have been conducted of the mechanical behavior of existing full-scale wooden 123 KV 13L cross-arms used in transmission towers. Two cases have been considered to be analyzed and tested accordingly. In the case of normal condition, standard load 7.98 KN, with 8 organized steps with angle Θ = 54.2º at YZ plan from Y-axis were applied. While Fr = 16 KN with 16 organized steps with angle Θ = 12.6 º at the horizontal plane, α = 17.57 º at the vertical plane was applied for broken wire condition. The numerical results of the simulation have proven that the experiments were confident for normal and broken wire conditions are 93 % and 98.2 % respectively. To improve the existing design of cross-arm structure, an integrated TRIZ–Morphological Chart–ANP approach was used to establish four (4) new concepts of cross arms of transmission towers. In a conceptual design phase, a solution was developed through employing the TRIZ model according to TRIZ 40 techniques. After precise analysis, the output of the selection process of the conceptual design was further validated, where conceptual design 2 was ranked optimal in all three processing scenarios. Bracket structure P1048 by UNISTRUT® has been followed as a guide to be modified through conducting some modifications by employing systematic exploitation of proven ideas or experience. The modified design of the structure of the bracket was analyzed by FEM using static structural tool data from analyzing process were used to specify the thickness of the bracket structure to be used in the final design. Finally, the improved 13L 123KV Cross-arm structure has been investigated with experimental and numerical load-deflection behavior for the whole structure. Two scenarios have been conducted broken and normal wire conditions. the experimental results showed that the maximum value deflection at the normal condition for tangential and radial deflection is 11.6 mm and 11.5 mm respectively. Numerical results of simulation have proven that the experiments were confident for broken and normal wire conditions are 98.7 % and 91.4 % respectively.